2017
DOI: 10.1016/j.esxm.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Bone Marrow–Derived Mesenchymal Stem Cells Reduces Erectile Dysfunction Following Cavernous Nerve Injury in Rats

Abstract: IntroductionIntravenous preload (delivered before cavernous nerve [CN] injury) of bone marrow–derived mesenchymal stem cells (MSCs) can prevent or decrease postoperative erectile dysfunction (J Sex Med 2015;12:1713–1721). In the present study, the potential therapeutic effects of intravenously administered MSCs on postoperative erectile dysfunction were evaluated in a rat model of CN injury.MethodsMale Sprague-Dawley rats were randomized into 2 groups after electric CN injury. Intravenous infusion of bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
(40 reference statements)
1
29
0
Order By: Relevance
“…Puissant and his colleagues suggested Nrf2 specificity to combine in P62 promoter of the antioxidant response element, promote the expression of P62, then combine with LC3, and activate autophagy [29]. Chunjuan Song and colleagues found that autophagy under oxidative stress was thought to be self-regulation of cells against harmful stimuli [30]. Our results suggest that probucol could increase Beclin1 and LC3-II levels and decrease the levels of P62 under oxidative stress.…”
Section: Discussionmentioning
confidence: 58%
“…Puissant and his colleagues suggested Nrf2 specificity to combine in P62 promoter of the antioxidant response element, promote the expression of P62, then combine with LC3, and activate autophagy [29]. Chunjuan Song and colleagues found that autophagy under oxidative stress was thought to be self-regulation of cells against harmful stimuli [30]. Our results suggest that probucol could increase Beclin1 and LC3-II levels and decrease the levels of P62 under oxidative stress.…”
Section: Discussionmentioning
confidence: 58%
“…Intravenous infusion of green fluorescent protein (GFP)-labelled allogeneic BMSCs was also effective in preventing corpora cavernosa fibrosis in a bCNI rat model 143 . Interestingly, following infusion, BMSC homing to the MPGs and injured cavernous nerves was observed.…”
Section: Effect On Fibrosis Refsmentioning
confidence: 99%
“…Puissant and his colleagues suggested that Nrf2 speci city to combine in P62 promoter of the antioxidant response element, promote the expression of P62, then combine with LC3 and activate autophagy [29]. Chunjuan Song and colleagues found that autophagy under oxidative stress was thought to be self-regulation of cells against harmful stimuli [30]. Our results suggest that probucol could increase Beclin1 and LC3-II levels and decrease the levels of P62 under oxidative stress.…”
Section: Discussionmentioning
confidence: 57%